Answer:
x= -3
y= -2
Explanation:
(1) x + 2y= -7
(2) 3x - 8y= 7
Balance a term in both equations for elimination
Equation (1) x (3) 3x + 6y= -21
Equation (2) x (-1) -3x + 8y= -7
After the calculation, it will result to:
14y= -28
Divide both sides by the coefficient of y
This will result to:
y= -2
From equation (1):
x + 2y= -7
Insert the unit of y (-2)
x + 2(-2)= -7
x - 4= -7
Collect like and unlike terms
x= 4 -7
x= -3
TO CHECK:
3x - 8y= 7
Insert the solved units
3(-3) - 8(-2)= 7
-9 - (-16)= 7
-9 + 16= 7
16 - 9= 7
CORRECT!!!